Synthesis and cyclic voltammetry of 1,2,3-trisubstituted bis(cyclopentadienyl)zirconium dichlorides - Rausch, Bernhard J.; Gleiter, Rolf; Rominger, Frank (Journal of organometallic chemistry, 2002)
The synthesis of the 1,2,3-trisubstituted cyclopentadienes 3-10 and their corresponding zirconocene dichlorides 11-18 from commercially available internal alkynes is presented. The solid state structures of the differently substituted zirconocenes 11-13 and 15-17 were examined by means of X-ray analysis. The bite angles have shown not to be dependent on the substitution pattern of the cyclopentadienyl ligand. Cyclic voltammetry was used to measure the effect of introducing electron withdrawing and donating groups at the five membered ligand on the Lewis acidity of the zirconium central atom.
Gesehen am 30.10.2020